MORPHOLOGICAL ANALYSIS OF ENGLISH COMPOUNDING IN JEEVA KLUI RESORT WEBSITE - Yessy Purnamasari (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2018)
In an English text, the variation of words are used in many kinds of word-formation. A text may consists of simple, compound, complex, or compound-complex sentences. There are also variation of phrases, clauses, or compounding to make the text becomes richer. However, when it comes to a text, those way cannot be applied in general. There are several aspects that distinguish whether it is a noun or it is a phrase. Thus, this research is expected to gives clear information in how a text in a website uses compounding as the element of its text. The research objectives are (1) to identify the kinds of compounding words found in the Jeeva Klui Resort’s official website based on the part of of speech of its constituent and (2) to identify the kind of compounding words found in the Jeeva Klui Resort’s official website based on the semantical relationship between the compound and its head. This research uses descriptive qualitative method which goal is a comprehensive summarization. The study focuses on the pronuciation of plural nouns in a text. The data, is taken from the official website of Jeeva Klui Resort which can be accessed through www.jeevaklui.com. For the linguistic studies, the theoretical benefit of this research is to give information about the use of English coumpounding in the text.